Effects of Exercise Training on Vascular Inflammatory Markers in High-fat Diet-induced Obese Rats - Kijin Kim (Asian Society of Kinesiology, 2020)
OBJECTIVES The purpose of this study was to confirm the positive effects on the inflammatory expression and functional changes of blood vessels by aerobic exercise training and dietary control in high-fat diet induced obese rats. METHODS Forty 10-week-old male Wistar rats were treated with high-fat diet for 6 weeks, followed by 4 groups as sedentary + chow diet group (Chow), sedentary + high fat diet group (HFD), exercise + chow diet group (Chow-Ex), high fat diet + Exercise group (HFD-Ex) after obesity induction. After treadmill running exercise and dietary treatment were performed for 8 weeks, body composition, endurance performance and muscular endurance, blood glucose, CRP, NO, insulin, eNOS, iNOS, protein expression of IL-6 and TNF-α in aortic vascular tissues was analyzed. RESULTS High-fat diet intake leads to an increase in body weight and visceral fat, an increase in insulin resistance and an increase in inflammation factors. The blood NO level was significantly higher (p <0.05) in the HFD and Chow groups than in the non-exercise group. Blood insulin levels were significantly higher (p <0.05) in the HFD group without exercise than in all other groups. Blood eNOS activity was significantly higher (p <0.05) in the HFD and Chow groups than in the non-exercise group. The expression level of IL-6 protein in the vascular tissues was significantly higher (p <0.05) in the HFD group without exercise than the other groups. The expression level of TNF-α was significantly lower (p <0.05) in the HFD and Chow groups than in the non-exercise group. CONCLUSIONS The results of this study confirmed that exercise training through aerobic exercise and dietary control may help to reduce inflammatory expression and improve vascular endothelial function in high-fat diet induced obese rats.